Common Mechanisms of Developmental Reprogramming in Plants—Lessons From Regeneration, Symbiosis, and Parasitism - Ichihashi, Yasunori; Hakoyama, Tsuneo; Iwase, Akira; Shirasu, Ken; Sugimoto, Keiko; Hayashi, Makoto (Frontiers in Plant Science, 2020)
Most plants are exquisitely sensitive to their environment and adapt by reprogramming post-embryonic development. The systematic understanding of molecular mechanisms regulating developmental reprogramming has been underexplored because abiotic and biotic stimuli that lead to reprogramming of post-embryonic development vary and the outcomes are highly species-specific. In this review, we discuss the diversity and similarities of developmental reprogramming processes by summarizing recent key findings in reprogrammed development: plant regeneration, nodule organogenesis in symbiosis, and haustorial formation in parasitism. We highlight the potentially shared molecular mechanisms across the different developmental programs, especially a core network module mediated by the AUXIN RESPONSIVE FACTOR (ARF) and the LATERAL ORGAN BOUNDARIES DOMAIN (LBD) family of transcription factors. This allows us to propose a new holistic concept that will provide insights into the nature of plant development, catalyzing the fusion of subdisciplines in plant developmental biology.